Does environmental management capability of Chinese industrial firms improve the contribution of corporate environmental performance to economic performance? Evidence from 2010 to 2015. (20th January 2017) - Liang, Dapeng; Liu, Tiansen
Abstract: As a powerful industrial country, the environmental performance of Chinese industrial firms is continuously being concerned by the international community. In this paper, we select 1310 social responsibility reports of Chinese industrial firms published from 2010 to 2015 as the sample with the aim to explore whether corporate environmental management capability can improve the contribution of environmental performance to economic performance (net profit rate)? Conclusions show that the level of environmental performance and environmental management capability of Chinese industrial firms are generally low, and concerning on environment does not significantly improve economic performance as a whole. Also, the moderating effect of environmental management capability improving the economic value of environmental performance is limited at present. However, with the environmental management capability becoming stronger, the contribution of environmental performance to economic performance has gradually improved, which is embodied when this capability is stronger than samples' average, it improves the contribution of energy-saving performance and environmental management legitimacy performance to net profit rate; while when it is lower than that, no any category of environmental performance can significantly and positively contribute to net profit rate. Empirical results imply that Chinese industrial firms should actively improve the level of environmental management capability. Highlights: We select 1310 social responsibility reports of Chinese industrial firms published from 2010 to 2015 as the sample. We apply the Content Analysis Method to evaluate corporate environmental performance. Environmental management capability can moderate the contribution of environmental performance to economic performance. Stronger environmental management capability can better improve the economic value of corporate environmental performance.